2016
DOI: 10.1016/j.ijbiomac.2016.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Fucan-coated silver nanoparticles synthesized by a green method induce human renal adenocarcinoma cell death

Abstract: Polysaccharides containing sulfated L-fucose are often called fucans. The seaweed Spatoglossum schröederi synthesizes three fucans, among which fucan A is the most abundant. This polymer is not cytotoxic against various normal cell lines and is non-toxic to rats when administered at high doses. In addition, it exhibits low toxicity against tumor cells. With the aim of increasing the toxicity of fucan A, silver nanoparticles containing this polysaccharide were synthesized using a green chemistry method. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
19
0
4
Order By: Relevance
“…However, some authors have verified the amount of silver in the structure of nanoparticles containing other polysaccharides. In studies conducted by Amorim et al 27 and Chen et al, 38 7% and 6.7% of silver were found, respectively, in a fucan-coated nanoparticle composition and in nanoparticles synthesized with fungal exopolysaccharide. These values are lower than those obtained by us in our study using corn cob xylans.…”
Section: Synthesis Of Silver Nanoparticles With Xylan (Nano Xylan)mentioning
confidence: 89%
See 2 more Smart Citations
“…However, some authors have verified the amount of silver in the structure of nanoparticles containing other polysaccharides. In studies conducted by Amorim et al 27 and Chen et al, 38 7% and 6.7% of silver were found, respectively, in a fucan-coated nanoparticle composition and in nanoparticles synthesized with fungal exopolysaccharide. These values are lower than those obtained by us in our study using corn cob xylans.…”
Section: Synthesis Of Silver Nanoparticles With Xylan (Nano Xylan)mentioning
confidence: 89%
“…35,36 Similar to the use of xylan employed in this work, in other studies, the use of polysaccharides with reducing agents to synthesize silver nanoparticles has already been described. 27,28,37 Determination of the Composition of NX…”
Section: Synthesis Of Silver Nanoparticles With Xylan (Nano Xylan)mentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, they showed that the FN remained stable for 16 months. Other nanoparticles synthesized thus far have not been stable for so long, although nanoparticles containing sulfated polysaccharides have been described as particles stable for several months [ 11 , 17 ]. An important feature is to be able to maintain the stability of nanoparticles and their surface charge.…”
Section: Discussionmentioning
confidence: 99%
“…There are several brown seaweed species of the Dictyotales order on the Brazilian coast, of which Spatoglossum schröederi is one of the most commonly studied. Recently, Amorim et al [ 11 ] showed that AgNPs containing fucan from S. schröederi were more effective cytotoxic agents than the fucan alone, which indicated that the AgNPs could potentiate the fucan’s activities. Other Dictyotales, such as Dictyota mertensii , contain antioxidant, antiproliferative, and immunomodulatory SSPs [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%